The Effect Of Online Game Addiction On Adolescent Social Interaction In Marga Jaya Village, Padang Jaya District, Bengkulu Utara Regency - Yudha Amanda Oktori; Asnawati Asnawati; Sri Narti (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to examine the online game addiction to adolescent social interactions in Marga Jaya village, Padang Jaya district, North Bengkulu district. This study uses quantitative research methods using questionnaires as a tool to obtain the necessary data. In this study using statistical calculations using simple linear regression analysis. The negative results of online games have a significant (opposite) effect on adolescent social interactions, this is based on the t test which shows the significance of t count < t table, or (-10.354) < (-1.994) ) which means that the lower addiction to playing online games respondents, social interaction remains good, so the hypothesis is good that there is an influence between online game addiction (X) on adolescent social interaction (Y).